Dual function of UPF3B in early and late translation termination - Neu-Yilik, Gabriele; Kerschgens, Kathrin; Hentze, Matthias W.; Kulozik, Andreas (The EMBO journal, 2017)
Nonsense-mediated mRNA decay (NMD) is a cellular surveillance pathway that recognizes and degrades mRNAs with premature termination codons (PTCs). The mechanisms underlying translation termination are key to the understanding of RNA surveillance mechanisms such as NMD and crucial for the development of therapeutic strategies for NMD-related diseases. Here, we have used a fully reconstituted in vitro translation system to probe the NMD proteins for interaction with the termination apparatus. We discovered that UPF3B (i) interacts with the release factors, (ii) delays translation termination and (iii) dissociates post-termination ribosomal complexes that are devoid of the nascent peptide. Furthermore, we identified UPF1 and ribosomes as new interaction partners of UPF3B. These previously unknown functions of UPF3B during the early and late phases of translation termination suggest that UPF3B is involved in the crosstalk between the NMD machinery and the PTC-bound ribosome, a central mechanistic step of RNA surveillance.